Discontinuation of long acting reversible contraceptive use and its determinants among women in Ethiopia: Systematic review and meta-analysis - Gebeyehu, Natnael Atnafu; Tegegne, Kirubel Dagnaw; Biset, Gebyaw; Sewuyew, Dagne Addisu; Alemu, Biresaw Wassihun; Yitayew, Alemker Mola (Frontiers in Public Health, 2022)
Out of 654 studies assessed, 20 met our criteria and were included in the study. The total number of study participants was 8780. The pooled prevalence of discontinuation of long acting reversible contraceptive use was 36.94% (95%CI: 28.547 -45.326). According to sub-group analysis, Amhara region (45%) and institution-based studies (47.9%) had the highest prevalence. The most common reason for contraceptive discontinuation was negative side effect (42.3%). Women experienced side effects (AOR=2.833:95%CI:2.005-4.003), didn’t receive counseling on side effects (AOR=2.417; 95%CI: 1.591 - 3.672), didn’t appoint follow up (AOR=2.820; 95%CI: 2.048 - 3.881), dissatisfied with the given service (AOR=5.156; 95%CI :3.644-7.296), and a desire to be pregnant (AOR=2.366; 95%CI: 1.760-3.182) were predictors of discontinuation of contraceptives.